Analisis Rasio Likuiditas Dan Rasio Profitabilitas (Studi Pada PT Mayora Indah, Tbk Tahun 2018-2020) - Melisa A Putri; Aras Tulip; Imam Suroso; Tutik Pebrianti; Indah Mawarni (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the level of liquidity ratios and profitability ratios at PT Mayora Indah, Tbk. This study uses quantitative data, namely the report of PT Mayora Indah, Tbk for the 2018-2020 period. Data collection techniques in this study were in the form of documentation and observation of financial statements and data analysis using descriptive analysis. The results of the study indicate that it is necessary to evaluate the dimensions of the cash ratio, basic earning power, return on assets and return on equity so that in the coming year it will increase.